Evaluation of physical properties of glass ionomer cement modified by ethanolic extract of propolis - Pratiwi, Deviyanti; Salim, Richentya Feiby; Putri, Tansza Permata Setiana; Hasan, Akhmad Endang Zainal (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Glass ionomer cement (GIC) is a dental material often used in clinical practice. However, its use is limited due to its drawbacks. Natural resources such as propolis have been used to mainly enhance GIC’s antibacterial properties, but other properties attributed to this enhancement also require evaluation. Purpose: The study aims to evaluate the surface hardness, the surface roughness, and the water absorption of GIC containing ethanolic extract of propolis (EEP) from Trigona spp. Methods: Samples in this study were divided into four groups: GIC (control group); GIC + 25% EEP; GIC + 30% EEP; and GIC + 35% EEP. Surface roughness was measured using a surface roughness tester. Surface hardness was measured using a micro-Vickers hardness tester. Water absorption was measured by weighing the samples before and after immersion in distilled water. Surface characterization was carried out using a scanning electron microscope (SEM). Data was statistically analyzed using the Shapiro–Wilk normality test and one-way variance analysis along with the post-hoc Tukey’s test to determine significant differences between all four samples. Results: The statistical test showed significant differences in surface hardness and surface roughness between the control group and the GIC + EEP group. However, the test demonstrated no significant differences in water absorption between the control group and the GIC + EEP group. Conclusion: The addition of EEP to conventional GIC can affect its physical properties.